Correlations Between Vestibular Function and Imaging of the Semicircular Canals in DFNA9 Patients - Ihtijarevic, Berina; Janssens de Varebeke, Sebastien; Mertens, Griet; Dekeyzer, Sven; Van de Heyning, Paul; Van Rompaey, Vincent (Frontiers in Neurology, 2020)
Background and Purpose: Radiologic abnormalities on computed tomography (CT), including narrowing or sclerosis of the semicircular canals (SCCs), and T2-weighted magnetic resonance imaging (MRI), including signal loss in the SCC, have been reported as potential biomarkers in patients with P51S mutations in the COCH gene (i.e., DFNA9). The aim of our study was to correlate caloric responses through electronystagmography (ENG) data with imaging results in DFNA9 patients. Materials and Methods: A retrospective study was performed in 45 patients; therefore, 90 ears with P51S mutations in the COCH gene were tested. Caloric responses and CT and MRI data were analyzed from June 2003 until May 2014. More than half of patients (54%) were candidates for cochlear implantation. Results: In our population, 91% of tested ears had sclerotic lesions and/or narrowing in one or more SCCs on CT scan. All tested ears had narrowing or signal loss in at least one SCC on T2-weighted MRI. The lateral SCC was affected in 87% on CT scan and 92% on MRI. However, in 83% of tested ears, all three SCCs were affected on MRI. Furthermore, in 77% of tested ears, caloric responses were reduced bilaterally, while 11.5% showed unilateral hypofunction and the other 11.5% had normal caloric responses. CT abnormalities correlated with hypofunction of caloric responses. This statistically significant difference was present if abnormalities were observed in at least one of the SCCs as well as in ipsilateral lateral SCC function loss. MRI abnormalities in at least one of the SCCs correlated with ENG hypofunction, but there was no direct correlation between lateral SCC abnormalities on MRI and caloric responses of the investigated lateral canal. Conclusion: Our retrospective analysis confirms the presence of CT and MRI abnormalities in DFNA9 patients with the P51S mutation in the COCH gene. A correlation between these radiologic features and vestibular function (tested by means of caloric response) was found in this population.